1996
DOI: 10.1088/0031-9155/41/1/009
|View full text |Cite
|
Sign up to set email alerts
|

The calibration of CT Hounsfield units for radiotherapy treatment planning

Abstract: Computer tomographic (CT) scans are used to correct for tissue inhomogeneities in radiotherapy treatment planning. In order to guarantee a precise treatment, it is important to obtain the relationship between CT Hounsfield units and electron densities (or proton stopping powers for proton radiotherapy), which is the basic input for radiotherapy planning systems which consider tissue heterogeneities. A method is described to determine improved CT calibrations for biological tissue (a stoichiometric calibration)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
935
2
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 904 publications
(954 citation statements)
references
References 12 publications
6
935
2
11
Order By: Relevance
“…The pCT and cCBCT image intensities for each voxel were converted to relative proton stopping powers using the stoichiometric calibration method, (2) and a ray‐tracing technique was used to determine the water‐equivalent thickness (WET) between a given start and end point. Using the stopping power ratio approximation, (21) the WET through one voxel is the product of the relative stopping power (RSPi) and path length (ti) within that voxel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pCT and cCBCT image intensities for each voxel were converted to relative proton stopping powers using the stoichiometric calibration method, (2) and a ray‐tracing technique was used to determine the water‐equivalent thickness (WET) between a given start and end point. Using the stopping power ratio approximation, (21) the WET through one voxel is the product of the relative stopping power (RSPi) and path length (ti) within that voxel.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to multislice fan‐beam CT, the Hounsfield units (HUs) in a CBCT image are highly sensitive to the effects of beam hardening and X‐ray scatter within the patient. Since the proton stopping power is calibrated to the HU, (2) a high degree of HU accuracy is desirable to minimize proton range uncertainty. The HU accuracy of CBCT technology currently is not accurate enough to be used directly for calculation of the water‐equivalent thickness (WET) or resultant proton dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The measured CT numbers were then sorted by the tube potential at which they were acquired and a mean CT number was calculated for each material averaged over all the phantom setups scanned. Three CT number‐PSPR tables were produced from the mean CT number data, using the stochiometric method described by Schneider et al (6) …”
Section: Methodsmentioning
confidence: 99%
“…Schneider et al (6) cited the results presented by McCullough and Holmes, (7) showing that the CT number does not significantly change with scan energy as justification for not including it in their development of the stochiometric method of calculating the CT number to PSPR conversion. Schaffner and Pedroni, (8) following the methods of Schneider and colleagues, did not include the CT scan kVp in their study.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a phantom with multiple inserts of these tissue‐equivalent materials (TEM) is used for the calibration measurement 5 , 6 . Several studies have also investigated the impact of the phantom insert materials on the HLUT accuracy either in FBCT or in CBCT 5 , 6 , 13 , 14 . These studies have shown that the use of materials that are not tissue‐equivalent can cause dose calculation errors.…”
Section: Introductionmentioning
confidence: 99%